Density and Composition of Species Clam (Tridacna sp.) Based on Coral Cover Conditions in Wawosunggu Waters, Konawe Regency - Ridwan Iskandar; Ermayanti Ishak; Dedy Oetama (Jurnal Biologi Tropis, 2023)
Kima is one of the protected marine resources. It has an ecological role as a water bio-filter and a symbiotic mutualism with coral reef ecosystems. The purpose of the research was to find out of species density and composition of clams (Tridacna sp.) based on the coral coverage on the waters island of Wawosunggu, South Konawe. The study was conducted in September 2022. Sampling was carried out at 3 observation stations based on habitat characteristics. The observing method used a transect belt/swept area. Data in the form of density, relative abundance of clams, and percentage of coral cover analyze by using MS software. Excel 2010. The number of clams obtained was 155 individuals consisting of 3 types, namely Tridacna maxima, T. squamosa, and T. crocea. The totally density (totals from species and locations) was 0.10 individuals/m2. The composition of all types of clams ranges from 25-56%. The percentage of coral cover obtained was grouped into 4 categories, namely fleshy seaweed/algae, hard coral, abiotic, and other biotic. The percentage of coral cover at all stations was dominated by the hard coral category (Acropora sp. and non Acropora sp.) with water quality conditions that supported the presence of clams and coral reefs.